FAKTOR-FAKTOR YANG MEMPENGARUHI KERUKUNAN ANTAR SUKU DI DESA SUNGAI KUNING KECAMATAN SINGINGI KABUPATEN KUANTAN SINGINGI - Mayalisa, Filsa; Dasrizal, Dasrizal; Nefilinda, Nefilinda (Pendidikan Geografi, 2013)
This research intent to get data, mengolah, menganalisis and working through about   Factor that regard intertribal reconciliation at Silvan An River Singingis district yellow my Regency Singingi Riaus pestle    seen of: 1 ) education Zoom and 2) social interaction and 3) living.             This observational type is deskriptip korelasional. This observational population is all patriarch that is at River Village yellow Singingis district my Regency Singingi Riaus pestle. Respondent Sample take is taken bases proposional random is sampling  which is bases its percentage which is 10 %, sample at Silvan An River Singingis district yellow my Regency Singingi Riaus pestle as much 72.  Analysis that is utilized is descriptive and statistical inferensial.               This research finds: 1 ) available education zoom influences to intertribal reconciliations at Silvan An River Singingis district yellow my Regency Singingi Riaus pestle, since t computing>  t table; (   2,396> 1,666)  level subjective force education to intertribal reconciliation comprises low( r = 0, 307) and contribution that is given as big as 2,2 %. 2)Available social interaction influence to intertribal reconciliation at Silvan An River Singingis district yellow my Regency Singingi Riaus pestle, since t computing>  t table; (   2,318> 1,666), interactions subjective force social to intertribal reconciliation comprise be( r = 0,408)  and contribution that is given as big as 9,1 %. 3) Available living influence to intertribal reconciliation at Silvan An River Singingis district yellow my Regency Singingi Riaus pestle, since t computing>  t table; (   1,895> 1,666),  livings subjective force to intertribal reconciliation comprise be( r = 0, 521) and contribution that is given as big as 14,9 %.   4 )   Available education zoom influence, social interaction, and ala living goes together to intertribal reconciliation at Silvan An River Singingis district yellow my Regency Singingi Riaus pestle because f computing  > F table;  ( 5,165> 2,74), drd subjective force variable that to intertribal reconciliation comprises be( r = 0, 421) and contribution that is given 10,9 %.